Unacceptable Visible Can Defects A Pictorial Manual - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Manuals of Food Quality Control, number 17. FAO. 1998. 30 pp.ISBN 92 5 104176 8.$8.00 o Euro 7.70FAO Publications,Viale delle Terme di Caracalla, 00100 Rome, Italy.Fax: +39 06 57053360Email: publications-sales@fao.org